2016
DOI: 10.1292/jvms.16-0036
|View full text |Cite
|
Sign up to set email alerts
|

Protection efficacy of the <i>Brucella abortus</i> ghost vaccine candidate lysed by the N-terminal 24-amino acid fragment (GI24) of the 36-amino acid peptide PMAP-36 (porcine myeloid antimicrobial peptide 36) in murine models

Abstract: Brucella abortus cells were lysed by the N-terminal 24-amino acid fragment (GI24) of the 36-amino acid peptide PMAP-36 (porcine myeloid antimicrobial peptide 36). Next, the protection efficacy of the lysed fragment as a vaccine candidate was evaluated. Group A mice were immunized with sterile PBS, group B mice were intraperitoneally (ip) immunized with 3 × 108 colony-forming units (CFUs) of B. abortus strain RB51, group C mice were immunized ip with 3 × 108 cells of the B. abortus vaccine candidate, and group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In the case of Brucella , it has been reported that Brucella S2 ghosts effectively elicit a pathogen-specific antibody response, enhancing IgG antibody and T cell responses in mice compared to inactivated bacteria ( 170 ). Kwon et al used a fragment of PMPA-36 (porcine myeloid antimicrobial peptide 36), named GI24, for B. abortus lysis and produced B. abortus ghosts, termed as B. abortus lysed cells ( 171 ). Due to the lack of genetic materials in BG vaccines, the horizontal transfer of antibiotic resistance genes or pathogenic islands to the resident gut flora does not occur.…”
Section: Other Vaccinesmentioning
confidence: 99%
“…In the case of Brucella , it has been reported that Brucella S2 ghosts effectively elicit a pathogen-specific antibody response, enhancing IgG antibody and T cell responses in mice compared to inactivated bacteria ( 170 ). Kwon et al used a fragment of PMPA-36 (porcine myeloid antimicrobial peptide 36), named GI24, for B. abortus lysis and produced B. abortus ghosts, termed as B. abortus lysed cells ( 171 ). Due to the lack of genetic materials in BG vaccines, the horizontal transfer of antibiotic resistance genes or pathogenic islands to the resident gut flora does not occur.…”
Section: Other Vaccinesmentioning
confidence: 99%